The Analysis of Criticism of Newspaper by Jokowi & Joe Biden regarding the Development of Covid-19 in the IDN Times and NY Times Online Media: Cross-Cultural Pragmatic Studies: Cross-Cultural Pragmatic Studies - Melisa Wulan Purnama; Ni Wayan Sartini (Journal of Pragmatics Research, 2023)
The research entitled "Analysis of Criticism of Newspaper by Jokowi & Joe Biden regarding the Development of Covid-19 in the IDN Times and NY Times Online Media: Cross-Cultural Pragmatic Studies" has two objectives, namely to analyze the functions and criticisms found in the online news articles IDN Times and NY Times and to explain the cultural differences and similarities between Indonesian and American society. This study analyzed ten IDN Times and NY Times news articles using a qualitative descriptive method. The data obtained in this study were through listening and note-taking techniques, because the data in this study were in the form of expressions that contain the function of speech and social criticism. Data validity uses theoretical triangulation. It was found 3 (three) assertive/representative functions in IDN Times and NY Times, 2 (two) commissive functions in IDN Times and 1 (one) commissive function in NY Times, 4 (four) expressive functions in IDN Times and 2 (two) expressive functions in NY Times, 2 (two) declarative functions in IDN Times and 1 (one) declarative function at the NY Times. There were also 3 (three) direct criticisms at the IDN Times and 5 (five) direct criticisms at the NY Times, as well as 2 (two) indirect criticisms at the IDN Times.